Platelet Inhibition and Bleeding in Patients Undergoing Non-Cardiac Surgery—The BIANCA Observational Study - Mahla, Elisabeth; Metzler, Helfried; Bornemann-Cimenti, Helmar; Prueller, Florian; Raggam, Reinhard B.; Pregartner, Gudrun; Berghold, Andrea; Baumann, Anneliese; Goeroeg, Christian; Gurbel, Paul A. (Thrombosis and Haemostasis, 2018)
Nearly 20% of patients will need non-cardiac surgery within 1 year of coronary stenting and their management is complicated by concomitant antiplatelet therapy. Platelet function testing may optimize the timing of surgery in these patients. In this prospective observational study, we explored the association between platelet reactivity and bleeding in patients undergoing non-cardiac surgery treated with clopidogrel with or without aspirin within 7 days before surgery. The timing of surgery was at the surgeon's discretion. Blood was drawn at induction of anaesthesia and platelet reactivity assessed by light transmittance aggregometry (LTA), vasodilator stimulated phosphoprotein (VASP) assay, Multiplate Analyzer and Innovance PFA-200. The primary endpoint was surgery-related thrombolysis in myocardial infarction (TIMI) bleeding. Among 197 patients enrolled, 72 and 12% underwent surgery within 24 and 48 hours of the last dose of clopidogrel, respectively. The median (interquartile range [IQR]) for pre-operative maximal adenosine diphosphate (ADP)-induced aggregation was 33.0% (21.0–57.5%), for VASP-platelet reactivity index was 61.5% (40.1–75.4%), for Multiplate was 22.0 (14.5–36.0) U*min and for Innovance PFA-200 was 224 (101.0–300.0) seconds. TIMI bleeding, observed in 25% of patients, decreased with increasing tertiles of platelet reactivity to ADP assessed by LTA (p = 0.031). Additionally, in a multivariable logistic regression analysis, platelet reactivity to ADP assessed by LTA was significantly associated with TIMI bleeding, as were age and urgency of surgery. These results demonstrate that in clopidogrel-treated patients, pre-operative platelet reactivity to ADP is associated with surgical bleeding risk. An objective assessment of pre-operative platelet function may optimize the timing of non-cardiac surgery in these patients.
Keywords: antiplatelet therapy; coronary artery disease; surgery; clopidogrel